PERANAN K 3 DALAM MANAJEMEN BENCANA - Sutanto, Sutanto (METANA, 2012)
A disaster is an event that occurs suddenly and is continuing that adversely affect the normal pattern of life or damage to the ecosystem. It is required emergency action and incredible to help and save people's lives and their environment. The incident could damage the structure and function of the crippling, resulting in damage and losses of lives and objects and facilities of community life. Disaster management is all efforts are embodied in an activity or series of activities undertaken to eliminate in part or all of the disaster and its impact and avoid the disaster that impacts can be minimized. Keywords : disarter management, mitigation, early worning